Association of baseline neutrophil-to-lymphocyte ratio with primary peritonitis in peritoneal dialysis patients - Hou Wen-juan; Tao Shu-man; Fang Wei-wei; Zhao Wen-man; Li Dan-dan; Liu Gui-ling (Linchuang shenzangbing zazhi)
Objective To retrospectively analyze whether a high neutrophil-to-lymphocyte ratio（NLR）was associated with the risk of initial peritonitis in peritoneal dialysis（PD）patients.Methods A total of 119 patients with end-stage renal disease underwent PD catheterization from August 2013 to July 2018 and regular follow–ups were conducted.They were divided into the groups of high NLR（NLR≥2.65）and low NLR（NLR<2.65）according to the median baseline level of NLR.The clinical data of two groups were compared.Logistic and linear regression models were employed for analyzing the correlation between baseline serum NLR and the occurrence of initial peritonitis.The diagnostic value of NLR to PD-associated peritonitis（PDAD）was evaluated by ROC curve.Results A total of 119 patients were recruited.The incidence of peritonitis was higher in high NLR group.Univariate logistic regression revealed a higher risk of peritonitis at baseline with a high level of NLR（OR=2.555,95%CI 1.684～3.878,P<0.01）had a higher risk of peritonitis.Multivariate analysis indicated that a high baseline level of NLR（OR=2.467,95%CI 1.439～4.232,P<0.01）was an independent risk factor for peritonitis.Univariate linear regression analysis showed that a high baseline level of NLR（standardized β=-0.352,P<0.01）was negatively correlated with dialytic age;multivariate linear regression analysis indicated that a high baseline level of NLR（standardized β=-0.340,P<0.01）was an independent risk factor for dialytic age.The area under the ROC curve was 0.813 when peritonitis predicted by baseline NLR peritonitis（P<0.01）and the maximal index was 0.595（sensitivity and specificity 71.4% and 88.1% respectively）.The corresponding optimal cut-off point was 3.64.Conclusions Higher serum baseline level of NLR is associated with an elevated risk of PDAP.